CRIMES AGAINST PERSONAL HEALTH: PROBLEMS OF CRIMINAL LEGAL THEORY AND PRACTICE - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Review of the monograph Katerynchuk K.V. "Crimes against personal health: problems of criminal law theory and practice."